Training tourism human resources during the Covid-19 pandemic: Opportunities and challenges for colleges and universities in Vietnam - Lê, Thanh Tú (Thông tin và truyền thông, 2023)
The Covid-19 pandemic have been making the hardest hit to the tourism industry and there have not been any signs of recovery. To develop the tourism industry, investing in human resources is very important, contributing to increase the attractiveness of the tourism industry, especially in the post- epidemic recovery period. In order to implement Central Resolution No.08 of the Politburo on developing tourism into a key economic sector, on May 28th, 2020, Prime Minister issued the No.24 instruction on promoting the development of skilled workforce, contributing to improve labor productivity and increasing the capacity of national competitiveness in the new situation. This issue has posed many difficulties to all tourism training colleges and universities all over the country. Within this article, the author desire to clarify the reality of training human resources in tourism, challenges and opportunities of tourism human resource training in the current period and in the future time, thereby contributing to the promotion of tourism industry to develop more and more sustainably.